Implementasi Sistem Pendeteksi Atrial Fibrillation Berbasis Arduino Uno Menggunakan Metode Support Vector Machine - Renita Leluxy Sofiana; Rizal Maulana; Fitri Utaminingrum (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2021)
Many cases of coronary heart disease that cause sudden death because the patient has a history of arrhythmias. In addition, 1 in 6 stroke patients are also caused by arrhythmias. According to cases that often occur in hospitals, Atrial Fibrillation arrhythmias are one of the factors that cause stroke because patients with Atrial Fibrillation arrhythmias have a five times greater risk of stroke because it can cause blockage of blood vessels. Prevention for this disease can be done by conducting early examinations so treatment can be done quickly. Currently, atrial fibrillation arrhythmia examination can only be done in a hospital, which is quite expensive and this examination cannot be done independently. This study uses the AD8232 sensor to generate ECG signals, the Arduino Uno as a data processor, and the LCD to display the results of the diagnosis,